Organochlorine pesticide, endosulfan induced cellular and organismal response in Drosophila melanogaster. - Sharma, A.; Mishra, M.; Shukla, A.K.; Kumar, R.; Abdin, M.Z.; Chowdhuri, D.K. (Journal of hazardous materials, 2012)
The effect of endosulfan (0.02-2.0?gmL(-1)) to Drosophila melanogaster (Oregon R(+)) at the cellular and organismal levels was examined. Third instar larvae of D. melanogaster and the strains transgenic for hsp70, hsp83 and hsp26 were exposed to endosulfan through food for 12-48h to examine the heat shock proteins (hsps), reactive oxygen species (ROS) generation, anti-oxidant stress markers and xenobiotic metabolism enzymes. We observed a concentration- and time-dependent significant induction of only small hsps (hsp23>hsp22) in the exposed organism in concurrence with a significant induction of ROS generation, oxidative stress and xenobiotic metabolism markers. Sub-organismal response was to be propagated towards organismal response, i.e., delay in the emergence of flies and decreased locomotor behaviour. Organisms with diminished locomotion also exhibited significantly lowered acetylcholinesterase activity. A significant positive correlation observed among ROS generation and different cellular endpoints (small hsps, oxidative stress markers, cytochrome P450 activities) in the exposed organism indicate a modulatory role of ROS in endosulfan-mediated cellular toxicity. The study thus suggests that the adverse effects of endosulfan in exposed Drosophila are manifested both at cellular and organismal levels and recommends Drosophila as an alternative animal model for screening the risk caused by environmental chemicals.